Job Satisfaction Mediates the Effect of Leadership and Workload on Employee Performance at PT. Bank Mandiri (Persero) Tbk. Denpasar Renon Branch - Wahyuni, Ni Luh Tri Dyah; Heryanda, Komang Krisna; Telagawathi, Ni Luh Wayan Sayang (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research explores job satisfaction as an intervening variable in the relationship between leadership, workload, and employee performance at PT Bank Mandiri (Persero) Tbk, Denpasar Renon Branch. In the banking sector, employee performance plays a vital role, as service excellence, productivity, and the achievement of organizational targets largely depend on the effectiveness of human resources. The study employs a quantitative method with a causal research design. Data were gathered through structured questionnaires administered to 125 employees and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings reveal that leadership exerts a positive and significant influence on employee performance, whereas workload has a significant negative impact. In addition, both leadership and workload significantly affect job satisfaction. Job satisfaction, in turn, shows a positive and significant effect on employee performance and fully mediates the influence of leadership and workload on performance. These results emphasize the importance of strong leadership and appropriate workload management in fostering job satisfaction, which ultimately enhances employee performance. This study contributes to the human resource management literature by reinforcing the mediating role of job satisfaction and provides practical insights for banking institutions in formulating leadership approaches and workload policies to improve employee performance.